Hermeticity testing of MEMS and microelectronic packages - Costello, Suzanne; Desmulliez, Marc P. Y., 1963- (Artech House integrated microsystems series., 2013)
Packaging of microelectronics has been developing since the invention of the transistor in 1947. With the increasing complexity and decreasing size of the die, packaging requirements have continued to change. A step change in package requirements came with the introduction of the Micro-Electro-Mechanical System (MEMS) whereby interactions with the external environment are, in some cases, required. This resource is a rapid, definitive reference on hermetic packaging for the MEMS and microelectronics industry, giving practical guidance on traditional and newly developed test methods. This book in.